High-throughput sequencing unravels placental vascular dysfunction and oxidative stress as mechanistic drivers of advanced maternal age-associated pregnancy - Sun, Xin; Chen, Yao; Hu, Feifei; Qiao, Yumeng; Wu, He; Su, Yao; Hu, Yue; Wu, Jie; Huang, Mingli (Frontiers in Genetics, 2025)
IntroductionWomen with advanced maternal age (AMA) face a higher risk of pregnancy complications including preeclampsia, fetal growth restriction, and preterm birth. While placental dysfunction is implicated, the underlying mechanisms remain unclear. This study employs high-throughput sequencing-based transcriptomics to investigate AMA-associated dysregulation in placental angiogenesis, exploring links to redox imbalance. Our goal is to establish mechanistic and functional links between altered gene expression and perinatal complications.MethodsPlacental pathology from 129 cases was analyzed to identify risk factors for maternal vascular malperfusion (MVM), a key pathological condition known to impair placental function. Building upon this pathological context, placental RNA-seq data from AMA and control pregnancies, combined with public datasets, were analyzed to identify differentially expressed genes (DEGs). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to identify functional pathways of dysregulated genes. Weighted gene co-expression network analysis (WGCNA) was utilized to detect AMA-related modules and hub genes, which were subsequently validated via Western blotting, qPCR, and immunohistochemistry (IHC).ResultsAnalysis of placental pathology (n = 129) identified advanced maternal age (AMA) as an independent risk factor for maternal vascular malperfusion (MVM) (OR = 3.022, 95% CI 1.337–6.832). RNA-seq revealed 731 differentially expressed genes (DEGs) in AMA placentas, which were enriched in energy metabolism, oxidative stress, angiogenesis, and NAD(P)H metabolic pathways. Weighted gene co-expression network analysis (WGCNA) identified six co-expression modules, of which the black module (most strongly AMA-associated) contained six hub genes (SIRT3, TLR6, AOX1, ARG1, CRYAB, HGF) exhibiting high intramodular connectivity. Functional studies confirmed that placental SIRT3 expression was markedly reduced in AMA (P < 0.05), while both impaired vascular perfusion and oxidative stress were significantly more severe.ConclusionOur findings indicate that reduced placental SIRT3 expression is a key molecular feature in advanced maternal age. This reduction may be related to increased risk of maternal vascular malperfusion and adverse pregnancy outcomes, potentially through mechanisms involving exacerbated oxidative stress and impaired placental vascular function; however, further studies are needed to clarify these associations.